THE INTERSECTION OF CHINA’S AND INDONESIA’S INTERESTS IN THE SOUTH CHINA SEA REGION (Вісник: Міжнародні відносини, 2024)
The article explores the intersection of interests between China and Indonesia in the South China Sea region. China’s interests revolve around its extensive territorial claims within Southeast Asia, while Indonesia, adhering to its longstanding policy of neutrality, aims to uphold regional stability and safeguard its sovereignty. The article analyzes the divergent security approaches of the two countries and examines the implications of disputes over the Indonesian Natuna Islands on China-Indonesia diplomatic relations.
Keywords: China, Indonesia, South China Sea, Natuna, territorial disputes, ASEAN